Hepatopulmonary syndrome and liver transplantation: the review and a case report - Yu. O. Malinovskaya; D. Dzhiner; E. N. Ostroumov; Ya. G. Moysyuk (Трансплантология (Москва))
Hepatopulmonary syndrome is a liver disease complication characterized by the clinical triad of an advanced chronic liver disease, a pulmonary vascular dilatation, and a reduced arterial oxygenation (hypoxemia: PaO2 less than 70 mm Hg at rest) in the absence of intrinsic cardiopulmonary disease. Precapillary vasodilatation, intrapulmonary angiogenesis and hyperdynamic circulation lead to arteriovenous shunting and reduced gas diffusion. In case of detecting macroscopic shunts, the pulmonary artery branch embolization could be performed. However, the hepatopulmonary syndrome can be cured nowadays by means of liver transplantation only. A 5-year survival in these patients is about 70%. The observed mortality is the highest during the surgery or early after, especially in patients with PaO2 lower than 50 mm Hg. It ranges from 8.5 to 29%. A prolonged oxygenation support is often required after liver transplantation using invasive or non-invasive ventilation, or even extracorporeal membrane oxygenation. In this review, we have focused on the recent advances in this field as described in available literature and have presented a case report of successful liver transplantation in a patient with a severe hepatopulmonary syndrome.